Performance Analysis of Recruitment Selection Strategy Based on Financial Performance with Cost Per Hire (CPH) Formulation - Achmad Brian Fajar Prayogi; Wisnu Panggah Setiyono (Dinasti Publisher, 2025)
The challenge of today's business organizations is to get the best employees at a low-cost performance. Recruitment costs are considered important and become part of a business strategy so that business processes run effectively and efficiently. So that knowledge of simultaneous recruitment and selection costs is needed by business organizations to support the achievement of a business vision globally. This research is a qualitative descriptive research design using the cost per hire (CPH) formulation as a formulation to calculate recruitment costs and a comparison of the findings was carried out in 5 different company objects in different fields. Based on the results of the research, it was found that hoteliers and plantation companies relatively have high selection recruitment costs, this is due to the needs of candidates, the majority of whom are specialists, so they require comprehensive selection recruitment procedures and involve external services in their implementation. In manufacturing companies, services and trade are relatively lower because the need for labor is generally relatively mass and non-skilled so the procedure is relatively simpler. In order for this study to produce broader findings data, it is hoped that future studies will use more company objects, more comprehensive calculation formulations, and by using broader cost indicators.